Service-oriented security framework for datacenter networks - Teng HU; Guanwen LI; Huachun ZHOU (Dianxin kexue)
With the large-scale deployment of datacenters in cloud computing,there is an increasing attention to their security issues.However,with the ossify deployment of traditional security devices,it is hard to meet the requirements of dynamical network security situation and copy with new kinds of security threats.Therefore,a service-oriented security framework for datacenter networks was proposed,which was able to compose the virtualized security functions flexibly and update the security policies dynamically based on virtualization technology and software-defined networking.With the implementation of prototype,the feasibility and availability of the proposed security framework was proved,and a solution to promote the flexibility and security of datacenter networks was provided.